The United States Marriage Market - Freiden, Alan (Journal of Political Economy, 1974)
For an analysis of the three forms of marriage recognized in Brazil, see Kogut (1972).Cheung (1972) has described the structure of property rights within marriage in Chinr. S34-'Note that a gain to marriage is not ruled out by decreasing returns to scale.